Take the 2-minute tour ×
TeX - LaTeX Stack Exchange is a question and answer site for users of TeX, LaTeX, ConTeXt, and related typesetting systems. It's 100% free, no registration required.

The code below was working for a while, but now, when I compile it, I get many "underfull box" warnings and "runaway argument" errors. Why?

\documentclass{article}

\usepackage{tikz}
\usepackage{amsmath}
\usepackage{amssymb}
\usepackage{fancyhdr}
\usepackage[T1]{fontenc}
\usepackage{fourier}

% document size parameters

\setlength{\oddsidemargin}{0.0in}
\setlength{\evensidemargin}{0.0in}
\setlength{\textheight}{8.4in}
\setlength{\textwidth}{6.5in}
\setlength{\voffset}{-0.40in}
\setlength{\headsep}{26pt}
\setlength{\parindent}{0pt}
\setlength{\parskip}{6pt}

% header information

\usepackage{environ}


\pagestyle{fancyplain}
\lhead{\large{{\bf MATH 122: Complex Analysis} }}
\rhead{\large{{\bf Spring Semester 2014}}}

% user defined macros

\renewcommand\Re{\operatorname{Re}}
\renewcommand\Im{\operatorname{Im}}
\newcommand\Arg{\operatorname{Arg}}


\newcommand{\secskip}{\vspace{6pt}}
\newcommand{\vect}[1]{\vec{#1}}

\begin{document}

\begin{Large} 
\large 
\flushright\textbf{{Kalvin Ogbuefi}}\\ 

\flushleft

\begin{center}
\textbf{Homework Assignment \# 4}\\
\textbf{Due: Wednesday, February 25, 2014}
\end{center}
\end{Large}

\begin{large}

When you are asked to prove or disprove a statement you \textbf{must} use appropriate proof structure with complete sentences.

\begin{enumerate}

\item Use the $\epsilon-\delta$ definition of limits to show the following limits:
\begin{enumerate}
\item $\lim_{z \to z_0} \Re(z) = \Re(z_0)$\\ 

Let $\epsilon > 0$, therefore we choose $\delta = \epsilon$\\
Then, if $0<|z-z_0|<\delta=\epsilon$, we have:\\ 
\begin{align*}
|Re(z)-Re(z_0)|<\epsilon \\
&=|Re(z-z_0)|<\epsilon\\
&=|Re(z-z_0)|\leq|z-z_0|<\delta=\epsilon\\
\text{as desired.}
\end{align*}

\item $\lim_{z \to 1} \frac{1}{(z-1)^3} = \infty$\\

Let $\epsilon > 0$, we choose $\delta = (\epsilon)^{1/3}$\\
Then, if $0<|z-1|<\delta$ we have:\\
$$|z-1|^{3}<\delta^{3}=\epsilon$$\\ 
and so:\\
$$|\frac{1}{z-1}|^{3}<\frac{1}{\epsilon}$$\\
\begin{align*}
\text{as desired.}
\end{align*}
\item $\lim_{z \to 0} \frac{\overline{z}^2}{z} = 0$\\

Let $\epsilon>0$, we choose $\delta=\epsilon$\\ 
Then for:\\
$$0<|z-0|=|z|<\delta=\epsilon$$
We have:
\begin{align*}
&|\frac{\overline{z}^{2}}{z}-0|\\
&=|\frac{\overline{z}^{2}}{z}|\\
&=\frac{|\overline{z}|^{2}}{|z|}\\
&=\frac{|{z}|^{2}}{|z|}\\
&=|z|<\epsilon\\
\text{as desired.}
\end{align*}


\end{enumerate}

\item Find the following limits:

\begin{enumerate}
\item $\lim_{z \to 2 + i} (z^2 - 4z + 2 + 5i)$\\

First we begin by expanding the complex numbers then apply limit:\\
\begin{align*}
&=\lim_{z \to 2 + i} (x^2-y^2+2ixy - 4x-4iy + 2 + 5i)\\
&=\lim_{z \to 2 + i} (x^2-y^2-4x+2+i(2xy-4y+5))\\
&=-3+i5\\
\text{as desired.}
\end{align*}

\item $\lim_{z \to i} \frac{z^4 -1}{z-i}$\\

We begin by rewriting the limit according to the roots of unity:\\ 
$$\lim_{z \to i} \frac{(z-i)(z+i)(z+1)(z-1)}{(z-i)}$$
Simplifying yields:\\
$$\lim_{z \to i} (z+i)(z-1)(z+1)$$
Applying the limit will yield:\\
$$=-4i$$
\item $\lim_{z \to i} \frac{z^2 + 4z + 2}{z + 1}$\\
We begin by rewriting the limit:\\ 
$$\lim_{z \to i} \frac{x^2-y^2+4x+2+i(2xy+4y)}{x+1+iy}$$\\
Now we take the complex conjugate\\
$$\lim_{z \to i} \frac{x^2-y^2+4x+2+i(2xy+4y)}{x+1+iy} \frac{(x+1)-iy}{(x+1)-iy}$$
Simplifying yields:\\
$$\lim_{z \to i} \frac{(x^2-y^2+4x+2)+y(2xy+4y)+i((2xy+4y)(x+1)+y(x^2-y^2+4x+2))}{(x+1)^2+y^2}$$
Applying the limit will yield:\\
$$=\frac{5+i5}{2}$$
\end{enumerate}

\item Let $f(z) = \frac{z^2}{|z|^2}$
\begin{enumerate}
\item Find the limit as $z \to 0$ along the line $y = x$. 

Let $f(z)=\frac{x^2-y^2+i(2xy)}{x^2+y^2}$\\ 

Along y=x, we have\\
\begin{align*}
&=\lim_{x \to 0} \frac{x^2-x^2+(2x x))}{x^2+x^2} \\
&=\lim_{x \to 0} \frac{i2x^2}{2x^2}\\
&=-i\\
\end{align*}
\item Find the limit as $z \to 0$ along the parabola $y = x^2$.\\
Along $y=x^2$ we find:\\
\begin{align*}
&=\lim_{x \to 0} \frac{x^2-x^4+(2x x^2))}{x^2+x^4} \\
&=\lim_{x \to 0} \frac{1-x^2+i2x}{1-x^2}\\
&=1\\
\end{align*}

\item What can you conclude about the limit of $f(z)$ as $z \to 0$?\\

Since the limits don't match the limit does not exist at that point.
\end{enumerate}

\item If $f(z)$ and $F(z)$ are two complex valued functions and
$$\lim_{z \to z_0} f(z) = w_0 \text{ and } \lim_{z \to z_0} F(z) = W_0$$
then show that
$$\lim_{z \to z_0} f(z) F(z) = w_0 W_0.$$\\

First of all, we have to use the $\epsilon-\delta$ definition of limits to use:\\
$$\lim_{z \to z_0} F(z) = W_0$$\\
There exists a $\delta$ s.t if $0<|z-z_0|<\delta$ then $|F(z)-W_0|<\sqrt{{\epsilon}}$\\
Likewise for:\\
$$\lim_{z \to z_0} f(z) = w_0$$\\
There exists a $\delta$ s.t if $0<|z-z_0|<\delta$ then $|f(z)-w_0|<\sqrt{{\epsilon}}$\\

So! If $\delta=min(\delta_1,\delta_2)$ , then:\\

\begin{align*}
&|f(z)-w_0||F(z)-W_0|\\
&=|(f(z)-w_0)(F(z)-W_0)|\\
&=|(f(z)-w_0)(F(z)-W_0)-0|\\
&<\sqrt{\epsilon}\sqrt{\epsilon}=\epsilon\\
\end{align*}
and so,\\
$$\lim_{z \to z_0} (f(z)-w_0)(F(z)-W_0)=0$$\\

Now to evaluate the limit using that answer we manipulate both sides to make the equation look like:\\
$$\lim_{z \to z_0} [(f(z)-w_0)(F(z)-W_0)+w_0W_0]=w_0W_0$$

If we foil the inside and use the properties of limits we'll find the solution to be:\\
$lim_{z \to z_0} [(F(z)f(z)-f(z)W_0-F(z)w_0+2w_0W_0]=w_0W_0$\\
$=lim_{z \to z_0} [F(z)f(z)]-lim_{z \to z_0} W_0[lim_{z \to z_0}f(z)]-w_0[lim_{z \to z_0}F(z)]+lim_{z \to z_0} 2w_0W_0=w_0W_0$\\
$$w_0W_0-2w_0W_0+2w_0W_0=$$\\
$$w_0W_0$$\\
So therefore through using the limit definition were we able to prove this limit.
\item Use mathematical induction, and the property you proved in the previous exercise to show:
$$\lim_{z \to z_0} z^n = z_0^n.$$\\

First we begin with the base case where $n=1$\\
$$lim_{z \to z_0} z^1=z_0^1$$\\

With the Inductive hypothesis we assume $n=k$ so $lim_{z \to z_0} z^k=z_0^k$.\\
Therefore we use this if $n=k+1$\\

$\lim_{z \to z_0}  z^{k+1}=\lim_{z \to z_0} z^{k}z^1$\\
=$(\lim_{z \to z_0} z^k)(\lim_{z \to z_0} z^1)$\\
=$z_0^{k}z_0$\\
=$z_0^{k+1}$\\

\item  Let $f(z)$ be continuous for all values of $z$. Prove that $g(z) = f(\overline{z})$ is also continuous for all $z$.
Since this is true:\\
$$lim_{z \to z_0} f(z)=f(z_0)$$\\ 

We want to show that this is also true!:\\

$$lim_{z \to z_0} f(\overline{z})=f(\overline{z_0})$$\\ 

So, $|f(z)-f(z_0)|<\epsilon and |f(\overline{z})-f(\overline{z_0)|$\\

So, since:\\

\begin{align*}
&|z-z_0|\\
&=|\overline{z-z_0}|\\
&=|\overline{z}-\overline{z_0}|\\
\end{align*}


We have $0<|\overline{z}-\overline{z_0}|<\delta$ and so\\

$f(\overline{z})-f(\overline{z_0})<\epsilon$





\item Determine where the following functions are continuous:
\begin{enumerate}
\item $\frac{z+1}{z^2+1}$
\item $\frac{z^2 + 6z + 5}{z^2 + 3z + 2}$
\end{enumerate}

\item Are there any points where $f(z) = (\overline{z})^2$ is differentiable?  By definition the derivative (if it exists) is defined by the following limit:

$$\lim_{\Delta z \to 0} \frac{ f(z_0 + \Delta z) - f(z_0)}{ \Delta z} $$

Decide for yourself if the limit exists by considering the following:

\begin{enumerate}
\item Determine the limit as $z \to z_0$ along vertical lines:

$$\lim_{\Delta z \to 0} \frac{f(z_0 + \Delta z) - f(z_0)}{ \Delta z} = \lim_{\Delta y \to 0} \frac{ f\left( x_0 + i (y_0 + \Delta y)\right) - f(x_0,y_0)}{ i \Delta y}$$

\item Determine the limit as $z \to z_0$ along horizontal lines:

$$\lim_{\Delta z \to 0} \frac{f(z_0 + \Delta z) - f(z_0)}{ \Delta z} = \lim_{\Delta x \to 0} \frac{ f\left( (x_0 + \Delta x) + i y_0\right) - f(x_0,y_0)}{ \Delta x}$$


\item Decide for yourself where $f(z)$ is differentiable. 
\end{enumerate}

\end{enumerate}

\end{large}

\end{document}
share|improve this question

closed as off-topic by Werner, Mico, Svend Tveskæg, karlkoeller, Guido Feb 26 at 6:57

  • This question does not fall within the scope of TeX, LaTeX or related typesetting systems as defined in the help center.
If this question can be reworded to fit the rules in the help center, please edit the question.

1  
See line 212 (should be \overline{z_0}). –  Werner Feb 26 at 5:49
4  
This question appears to be off-topic because it is very localized and is not likely to help a broader audience. –  Werner Feb 26 at 5:50
1  
Welcome to TeX.SX! All the underfull boxes are due to improper use of \\. Use blank lines (or \par) to start new lines and \bigskip when you need more spacing. –  karlkoeller Feb 26 at 6:01

Browse other questions tagged or ask your own question.